Pandangan Jalaluddin Rakhmat terhadap Keadilan Sahabat: Sebuah Tinjauan Kritis: Jalaluddin Rakhmat’s Views on the Justice of the Prophet Muhammad’s Companions: A Critical Review - Sumardi, Edi; Fadlilah, Ahmad Rizqi (Journal of Islamic and Occidental Studies, 2024)
This article examines Jalaluddin Rakhmat's critical perspective on the concept of the justice of the Companions (‘adālah al-shaḥābah) in Islamic tradition and evaluates his arguments based on scholars' views. Jalaluddin Rakhmat rejects the generalization of the Companions' justice, considering them ordinary humans prone to mistakes. He critiques some Companions, such as Abu Hurairah and Ibnu Abbas, as mudallis and questions the political actions of other Companions like Abu Bakar and Muawiyah. This study employs a qualitative approach using literature review methods to analyze Jalaluddin Rakhmat’s works, hadith sources, and scholars' perspectives within the discipline of hadith studies to evaluate the validity of his criticisms. The analysis reveals that some of his views are based on misinterpretations or weak sources, such as equating mudallis with mursal shaḥābiyy, which are disciplinarily distinct in hadith science. His rejection of the concept of the Companions' justice impacts the reinterpretation of hadith and Islamic history, which is critically examined here to assess the validity of his arguments. This article emphasizes the importance of caution in critiquing the Companions, especially in maintaining ethical and methodological rigor, to understand their role in preserving the authenticity of Islamic teachings.